Tackling range uncertainty in proton therapy: Development and evaluation of a new multi-slit prompt-gamma camera (MSPGC) system - Youngmo Ku; Sehoon Choi; Jaeho Cho; Sehyun Jang; Jong Hwi Jeong; Sung Hun Kim; Sungkoo Cho; Chan Hyeong Kim (Nuclear Engineering and Technology, 2023)
In theory, the sharp dose falloff at the distal end of a proton beam allows for high conformal dose to the target. However, conformity has not been fully achieved in practice, primarily due to beam range uncertainty, which is approximately 4% and varies slightly across institutions. To address this issue, we developed a new range verification system prototype: a multi-slit prompt-gamma camera (MSPGC). This system features high prompt-gamma detection sensitivity, an advanced range estimation algorithm, and a precise camera positioning system. We evaluated the range measurement precision of the prototype for single spot beams with varying energies, proton quantities, and positions, as well as for spot-scanning proton beams in a simulated SSPT treatment using a phantom. Our results demonstrated high accuracy (<0.4 mm) in range measurement for the tested beam energies and positions. Measurement precision increased significantly with the number of protons, achieving 1% precision with 5 × 108 protons. For spot-scanning proton beams, the prototype ensured more than 5 × 108 protons per spot with a 7 mm or larger spot aggregation, achieving 1% range measurement precision. Based on these findings, we anticipate that the clinical application of the new prototype will reduce range uncertainty (currently approximately 4%) to 1% or less.